2008
DOI: 10.1080/01612840802182938
|View full text |Cite
|
Sign up to set email alerts
|

Positive and Negative Affect and Health Functioning Indicators among Older Adults with Chronic Illnesses

Abstract: Abstract:Emotional states have been linked with physical and mental health outcomes. In this study the role of positive and negative affect was investigated as determinants of health functioning for a community-dwelling sample of 153 older adults (age 60 or older) with chronic illnesses. High positive affect and low negative affect were found to be associated with lower levels of symptom distress, fewer depressive symptoms, higher daily activity scores, and higher perceived physical and mental health-related q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
40
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 45 publications
9
40
0
2
Order By: Relevance
“…These findings are congruent with previous studies that found positive affect was associated with higher pain self-efficacy, lower pain catastrophizing, and better health (Carver and Connor-Smith, 2010;Hu and Gruber, 2008;Pressman and Cohen, 2005). Since these individuals with positive affect are more likely to be confident in their own efforts in managing their pain, they may experience lower distress and higher quality of life.…”
Section: Discussionsupporting
confidence: 93%
“…These findings are congruent with previous studies that found positive affect was associated with higher pain self-efficacy, lower pain catastrophizing, and better health (Carver and Connor-Smith, 2010;Hu and Gruber, 2008;Pressman and Cohen, 2005). Since these individuals with positive affect are more likely to be confident in their own efforts in managing their pain, they may experience lower distress and higher quality of life.…”
Section: Discussionsupporting
confidence: 93%
“…Even though the path models made assumptions about the direction of relationships between constructs, the cross sectional nature of this study makes inferences of causal relationships inappropriate. In addition, other health-related psychosocial factors not included in this study, such as anxiety, depression (Fava et al, 2011), and negative affect (Hu & Gruber, 2008), could have been associated with the psychosocial factors and illness behavior examined in this study.…”
Section: Limitationsmentioning
confidence: 89%
“…As circunstâncias emocionais estão relacionadas com o funcionamento mental e físico. Verificou-se que em doenças crónicas (Hu & Gruber, 2008) que mais afeto positivo e menos afeto negativo estão associados com uma melhor saúde física e mental. Os resultados desta investigação não são consistentes em todos com estes resultados.…”
Section: Discussionunclassified